PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK â€œFUN THINKERS BOOKâ€ TEMA BERBAGAI PEKERJAAN - Riani, Rindiana Putri; Huda, Khoirul; Fajriyah, Khusnul (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2019)
The purpose of this study was to determine the validity of the product of developing thematic learning media Fun Thinkers Book on the theme of various fourth grade elementary school jobs. This research used research and development methods used to produce products and test the feasibility of media Fun Thinkers Book. This study used the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation. The problem was the lack of thematic learning media, when learning only used student books and LKS only so students are less interested, feel bored and make concentration The students only lasted a little while.The data were obtained through questionnaires, observations, and interviews.This study was conducted at the fourth grade in 3 elementary schools in the District of Pucakwangi, Pati, this study produced valid media with appropriate criteria in accordance with the results of the teacher response questionaire the percentage is 97.5% with very decent criteria and the results of the student questionaire responded 98.6% with very feasible criteria.